Impact of implant removal on quality of life and loss of correction in the treatment of traumatic fractures of the thoracolumbar spine - André El Saman; Simon Lars Meier; Florian Rüger; Jason Alexander Hörauf; Ingo Marzi (Brain and Spine)
Background: Benefit of implant removal in spine surgery remains unclear. While there is mostly consensus about necessity of implant removal in posterior-only stabilized patients, the effect of this measure in cases with combined anterior-posterior stabilization is undetermined. With this work we present a retrospective analysis of 87 patients with traumatic thoracolumbar vertebral fractures concerning quality of life (QOL), loss of correction (LOC) and range of motion (ROM). The effect of implant removal on the outcome 18–74 months after surgery was analyzed to determine how implant removal affects radiologic, functional and quality-of life-related parameters. Patients and methods: 87 patients suffering from a traumatic vertebral body fracture (T11 – L2) were included. Quality of life was determined using four different scoring systems (SF 36, VAS, Oswestry, LBOS). Clinical examination included range of motion. Radiologic findings were correlated with QOL. Results: Patients with removal of the internal fixator had a trend towards better range of motion than patients with posterior instrumentation left in place. Radiologic findings showed no correlation to QOL. Implant removal led to better values in Oswestry and SF-36. 69% of patients after removal reported a reduction of their symptoms.All patients with persistence of severe pain after implant removal belonged to subgroup II.2 (anterior monosegmental fusion with bone graft) Conclusion: Removal of the internal fixator can lead to a reduction of symptoms. Patient selection is crucial for successful indication. Radiologic findings do not correlate with QOL.